2011
DOI: 10.1172/jci45563
|View full text |Cite
|
Sign up to set email alerts
|

Mice overexpressing BAFF develop a commensal flora–dependent, IgA-associated nephropathy

Abstract: B cell activation factor of the TNF family (BAFF) is a potent B cell survival factor. BAFF overexpressing transgenic mice (BAFF-Tg mice) exhibit features of autoimmune disease, including B cell hyperplasia and hypergammaglobulinemia, and develop fatal nephritis with age. However, basal serum IgA levels are also elevated, suggesting that the pathology in these mice may be more complex than initially appreciated. Consistent with this, we demonstrate here that BAFF-Tg mice have mesangial deposits of IgA along wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
165
1
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 232 publications
(181 citation statements)
references
References 63 publications
8
165
1
1
Order By: Relevance
“…153 Our work has implicated IgA in kidney pathogenesis, and an important question is whether IgA C PC themselves are found in this location. 63 Moreover, although the cecum and colon are relatively poor in IgA C PC in the steady-state, in responses to Citrobacter rodentium IgA C PC quickly accumulate in the cecum/colon in as little as 36 hours. 1 The fact that in the steady state approximately 40% of PC in human BM are IgA C PC that express CCR4 as well as the b7 integrin and CCR10 may suggest a contribution of mucosal PC to the BM compartment, however more research is needed to unambiguously determine where these PC were originally generated.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…153 Our work has implicated IgA in kidney pathogenesis, and an important question is whether IgA C PC themselves are found in this location. 63 Moreover, although the cecum and colon are relatively poor in IgA C PC in the steady-state, in responses to Citrobacter rodentium IgA C PC quickly accumulate in the cecum/colon in as little as 36 hours. 1 The fact that in the steady state approximately 40% of PC in human BM are IgA C PC that express CCR4 as well as the b7 integrin and CCR10 may suggest a contribution of mucosal PC to the BM compartment, however more research is needed to unambiguously determine where these PC were originally generated.…”
Section: Resultsmentioning
confidence: 99%
“…This results in a massive increase in IgA levels in the serum, and interestingly, a portion of this serum IgA appears to be specific for commensal organisms. 63 Mice that over-express BAFF exhibit kidney dysfunction resulting in hematuria, proteinuria and premature death. 64,65 We observed that if BAFF-transgenic mice were crossed to an IgA-deficient background, kidney pathology was largely attenuated, suggesting that over-production of IgA may have a pathological consequence not unlike in the human disease IgA nephropathy.…”
Section: Plasma Cell-intrinsic Mechanisms Of Survivalmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on our results, BAFF production by neutrophil B helper cells, by promoting B cellmediated lymphotoxin production, may also affect CD169 ϩ cell survival and subsequently enforce antigen amplification and presentation. Furthermore, BAFF overexpression has been linked to a variety of autoimmune diseases, such as rheumatoid arthritis, lupus erythematosus, and Sjögren syndrome (5,(43)(44)(45). A clinically used BAFF-blocking antibody, belimumab, is effective in treating some lupus patients (46), and potentially, some clinical efficacy of BAFF neutralization in lupus patients may be due to effects on CD169 ϩ macrophages.…”
Section: Discussionmentioning
confidence: 99%
“…This locus contains the gene TNFS 13 that codes a proliferation-inducing ligand (APRIL). APRIL might determine the proliferation of IgA-producing cells [29,30] and APRIL serum levels may be higher in subjects affected by IgAN [31] . A second locus on chromosome 22q12 affects the circulatory IgA load and the susceptibility to develop IgAN [19] .…”
Section: Immunity Mucosa-relatedmentioning
confidence: 99%